2015
DOI: 10.1097/mot.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as master regulators of immune responses in transplant recipients

Abstract: miRNA-based diagnosis is a fast-moving field with new miRNA signatures being identified each day. Recent advances have also been successful at taking a few of these miRNAs to clinical trials for therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 109 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, some reports indicate that miRNA could directly regulate the expression of viral genes, thus interfering with viral replication. 4 , 16 Sonkoly et al 17 found a close link between miRNAs and a chronic inflammatory skin disease that indicates the important immunomodulatory effect of miRNAs. These findings also reflect the mechanism by which miRNA regulates viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some reports indicate that miRNA could directly regulate the expression of viral genes, thus interfering with viral replication. 4 , 16 Sonkoly et al 17 found a close link between miRNAs and a chronic inflammatory skin disease that indicates the important immunomodulatory effect of miRNAs. These findings also reflect the mechanism by which miRNA regulates viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting this concept, serum miRNAs have been proposed as potential prognostic biomarkers in different transplantation settings [4,15,16]. Due to cohort constrains we were not able to assess potential correlations between the miRNAs investigated in this study and other biomarkers, including inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 78%
“…First, our findings demonstrated that miR-124-3p was downregulated in HG-stimulated HRMECs. MiRNAs are major regulators in a variety of diseases (Kaul and Krams, 2015;Trionfini and Benigni, 2017). Specially, it has been confirmed that miRNAs exert pivotal functions in the initiation and development of DR. For example, miR-138-5p exerts a protective role the early DR by regulating NOVA1 (Bao and Cao, 2019).…”
Section: Discussionmentioning
confidence: 97%